2019
DOI: 10.1371/journal.pone.0226035
|View full text |Cite
|
Sign up to set email alerts
|

Snord94 expression level alters methylation at C62 in snRNA U6

Abstract: Understanding the regulation of development can help elucidate the pathogenesis behind many developmental defects found in humans and other vertebrates. Evidence has shown that alternative splicing of messenger RNA (mRNA) plays a role in developmental regulation, but our knowledge of the underlying mechanisms that regulate alternative splicing are incomplete. Notably, a subset of small noncoding RNAs known as scaRNAs (small cajal body associated RNAs) contribute to spliceosome maturation and function through g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Alternatively, the loss of 2 0 -O-methylations might affect unwinding kinetics of the U4/U6 duplex during spliceosome activation as many of the modifications map to the U4/U6 stem II (Figure 1B, left). Consistently with present studies, loss of an individual U6 2 0 -O-methylation has been linked to defects or alterations in splicing in a subset of introns (Ogren et al, 2019). The nature of how the possible structural perturbations translate into the observed changes in splicing needs further investigation.…”
supporting
confidence: 87%
“…Alternatively, the loss of 2 0 -O-methylations might affect unwinding kinetics of the U4/U6 duplex during spliceosome activation as many of the modifications map to the U4/U6 stem II (Figure 1B, left). Consistently with present studies, loss of an individual U6 2 0 -O-methylation has been linked to defects or alterations in splicing in a subset of introns (Ogren et al, 2019). The nature of how the possible structural perturbations translate into the observed changes in splicing needs further investigation.…”
supporting
confidence: 87%
“… 41 When analyzing the biopsied umbilical arterial fibroblast cells, the expression of SNORD113-6 was much higher than controls. 41 More specifically, SNORD113-6 and the murine equivalent, AF357425, were believed to methylate tRNA Leu (TAA) and prevent the fragmentation of its original structure into smaller tRFs, based on the high-to-low ratio of tRNA Leu (TAA) to tRF Leu 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ( Figure 2 ). 41
Figure 2 The breakdown of tRNA in a eukaryotic cell When cells are exposed to stress hypoxia, tRNA molecules degrade into tRFs, molecules that can be detrimental to cellular health (bottom row).
…”
Section: The Effects Of Snornas On Trna and Trfsmentioning
confidence: 99%
“… 50 Another study demonstrated that SNORD94, a specific scaRNA, guides Cm62 in U6 snRNA and alters overall spliceosome function. 51 Whether scaRNA expression in TOF can be mechanistically induced to alleviate TOF symptoms deserves further attention.
Figure 3 Hearts of infants with TOF can have an abnormal hole located between the right and left ventricles, resulting in the pumping of deoxygenated blood through the aorta and into the body In the affected heart, it is believed that the underexpression of scaRNA1, SNORD94, and possibly other undiscovered sno-/scaRNAs may disrupt several molecular processes, such as splicing, transcription, and translation, as well as alter cellular products, such as spliceosomes, mRNA, rRNA, ribosomes, and proteins.
…”
Section: Role Of Snornas In Tofmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations strongly suggest that snoRNAs and snRNAs are necessary for normal cardiac development. Furthermore, Ogren et al reported that methylation in the target region of SNORD94 on U6 is decreased in right ventricular myocardium tissue of infants with TOF compared with that of the control ( Ogren et al, 2019 ). Additionally, cell culture experiments revealed that, by changing the levels of SNORD94, a corresponding change in methylation at C 62 within the snRNA U6 is produced.…”
Section: Role Of Snornas In Cvdmentioning
confidence: 99%